Specific molecular prenatal diagnosis for the CTG mutation in myotonic dystrophy. Issue 11 (November 1992) - Myring, J; Meredith, A L; Harley, H G; Kohn, G; Norbury, G; Harper, P S; Shaw, D J
Abstract : The results of DNA analysis for the specific mutation of myotonic dystrophy are reported in eight pregnancies (two studied retrospectively) in six families. Four results were normal; in the other four, large DNA expansions were found, comparable to the range seen in severely affected children with congenital onset of the disorder. The results agreed with those obtained by linked DNA markers in the six cases where they were available. We conclude that specific molecular prenatal diagnosis of myotonic dystrophy is feasible, and that an abnormal result may also give a guide to possible severity, though this should be interpreted with caution until greater experience is available.